MOTIVATION AMONG EMPLOYEES IN MULTINATIONAL CORPORATIONS - Al-Saqri, Zeina Taisir Abdel Hafiz; Vida, Viktória (Applied Studies in Agribusiness and Commerce, 2023)
Nowadays motivation plays a huge role amongst employees especially when we relate it to people working in multinational companies for example Pepsi, Coca Cola, Nescafe and many more. Motivation is a topic that relates to all of us. It is very essential for employers to seek and recognize what motivates an employee. Many people underestimate the benefits and importance of human resource management in their businesses or day-to-day life. When we talk about human resource management, we are talking about human capital. Human capital emphasises the ability, skills, and the personality of the person you are trying to recruit or employ. In this study, we wish to analyse the importance of how motivation stands out in employees in different types of offices/workforces. The different aspects in multinational corporations show different characteristics.